Oropharyngeal flora and chest infection after upper abdominal surgery. Issue 3 (March 1991) - Dilworth, J P; White, R J; Brown, E M
Abstract : The oropharyngeal flora was determined before and after operation in 127 patients undergoing upper abdominal surgery. Swabs of the oropharynx were obtained on the day before operation and on the first, third, and fifth postoperative days. Isolation of Haemophilus influenzae, Streptococcus pneumoniae, and coliforms was noted. In the 108 patients with the full series of throat swabs the incidence of oropharyngeal colonisation by H influenzae was 16% and was unchanged after operation. S pneumoniae was present in only 5.6 (six patients) before operation and the incidence fell to 1.9% (two patients). There was a transient rise in coliform colonisation postoperatively. Twenty four patients developed a chest infection. In eight a bacterial cause was established, in six H influenzae and in two S pneumoniae. There was a significant relation between the carriage of H influenzae before operation and development of a chest infection. H influenzae was also found more often in cigarette smokers. The presence of S pneumoniae or coliform organisms before surgery was not related to the development of infection. The high incidence of postoperative chest infection in cigarette smokers appears to be due in part to preoperative colonisation of the oropharynx by H influenzae.